2020
DOI: 10.1101/2020.05.19.20107532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Open Source Data Sets: A Comprehensive Survey

Abstract: In December 2019, a novel virus named COVID-19 emerged in the city of Wuhan, China. In early 2020, the COVID-19 virus spread in all continents of the world except Antarctica causing widespread infections and deaths due to its contagious characteristics and no medically proven treatment. The COVID-19 pandemic has been termed as the most consequential global crisis after the World Wars. The first line of defense against the COVID-19 spread are the non-pharmaceutical measures like social distancing and personal h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 95 publications
0
81
0
3
Order By: Relevance
“…CovidQA, a question-answering dataset was developed for covid 19 [8] . Shuja et al [9] have formulated research domain taxonomy and identified features of datasets concerning the type, methods, application. Santos et al [10] presented a dataset on COVID-19 in which research activities overview was provided so that it would be easy to find scientists and researchers who are active in the task of combating the disease.…”
Section: Related Workmentioning
confidence: 99%
“…CovidQA, a question-answering dataset was developed for covid 19 [8] . Shuja et al [9] have formulated research domain taxonomy and identified features of datasets concerning the type, methods, application. Santos et al [10] presented a dataset on COVID-19 in which research activities overview was provided so that it would be easy to find scientists and researchers who are active in the task of combating the disease.…”
Section: Related Workmentioning
confidence: 99%
“…In [637] , a public covid-19 X-Ray image data collection is presented in which the frontal and lateral view imagery and metadata such as the time since the first symptoms, ICU status, survival status, intubation status and hospital location are recorded. A survey on the existing open datasts are available in [638] . In [639] some open datasets for monitoring, modeling and forecasting the epidemic is provided.…”
Section: Datasetsmentioning
confidence: 99%
“…On the other hand, several institutions that own large collections of high-quality scans are often not inclined to anonymously share the data. As a result, in spite of some recent efforts in the literature [4,5], public COVID-19 CT datasets are still mostly limited in size and quality [6][7][8]. The lack of large and high-quality datasets in the field hampers the development and translation of the medical image analysis methodology developed in actual clinical practice.…”
Section: Introductionmentioning
confidence: 99%